Factors associated with secondary thoracotomy for hemostasis following lung surgery: a retrospective analysis - Xie, Junwei; Wang, Hongliang; Han, Tianci; Tong, Wei; Guo, Xiaoqi; Zhang, Min; Liu, Dongzhe; Zhang, Liang; Liu, Hongxu (Frontiers in Oncology, 2025)
PurposeThis study aimed to systematically investigate the causes and management of secondary thoracotomy for hemostasis following lung cancer surgery. Although infrequent, secondary thoracotomy can lead to prolonged hospitalization, increased costs, and additional patient trauma. However, prior research has been limited to case reports or experience-based summaries, lacking a comprehensive analysis of this issueMethodsA retrospective analysis was conducted on 39 patients who underwent secondary thoracotomy for hemostasis between January 2015 and December 2022 at the Cancer Hospital of China Medical University. Data analyzed included surgical methods, tumor staging, bleeding sites, and hemostasis techniques. Statistical analysis was performed using SPSS 26.0; logistic regression was used to identify risk factors.ResultsAmong 15,156 patients who underwent lung surgery, 39 (0.257%) required secondary thoracotomy. Key risk factors were pleural adhesions (adjusted odds ratio [aOR] = 20.00), history of smoking (aOR = 3.56), and male sex (aOR = 3.21). Most secondary thoracotomies occurred within 24 hours post-surgery, with bleeding primarily at adhesion release sites and lung parenchymal injury. Electrocoagulation and suture ligation were the main hemostasis methods. The incidence of secondary thoracotomy decreased from 0.458% in 2015 to 0.178% in 2022, and this decrease correlates with increased adoption of thoracoscopic surgery.ConclusionsSecondary thoracotomy for hemostasis is associated with specific risk factors such as pleural adhesions and history of smoking. This study highlights the importance of meticulous hemostasis, especially at adhesion sites and lung parenchymal injury. Advances in thoracoscopic surgery and surgical techniques have reduced secondary thoracotomy rates. Nevertheless, further research with larger samples is needed to explore the impact of metabolic diseases on this complication.